Ischemic Preconditioning Did Not Affect Central and Peripheral Factors of Performance Fatigability After Submaximal Isometric Exercise - Behrens, Martin; Zschorlich, Volker; Mittlmeier, Thomas; Bruhn, Sven; Husmann, Florian (Frontiers in Physiology, 2020)
The present study was designed to provide further insight into the mechanistic basis for the improved exercise tolerance following ischemic preconditioning (IPC) by investigating key-determinants of performance and perceived fatigability. Using a randomized, counterbalanced, single-blind, sham-controlled, crossover design, 16 males performed an isometric time-to-exhaustion test with the knee extensors at 20% maximal voluntary torque (MVT) after an IPC and a sham treatment (SHAM). Those who improved their time-to-exhaustion following IPC performed a time-matched IPC trial corresponding to the exercise duration of SHAM (IPCtm). Neuromuscular function was assessed before and after exercise termination during each condition (IPC, IPCtm, and SHAM) to analyze the impact of IPC on performance fatigability and its central and peripheral determinants. Muscle oxygenation (SmO2), muscle activity, and perceptual responses (effort and muscle pain) were recorded during exercise. Performance fatigability as well as its central and peripheral determinants were quantified as percentage pre-post changes in MVT (ΔMVT) as well as voluntary activation (ΔVA) and quadriceps twitch torque evoked by paired electrical stimuli at 100 and 10 Hz (ΔPS100 and ΔPS10·PS100–1-ratio), respectively. Time-to-exhaustion, performance fatigability, its determinants, muscle activity, SmO2, and perceptual responses during exercise were not different between IPC and SHAM. However, six participants improved their performance by >10% following IPC (299 ± 71 s) compared to SHAM (253 ± 66 s, d = 3.23). The time-matched comparisons (IPCtm vs. SHAM) indicated that performance fatigability, its determinants, and SmO2 were not affected, while effort perception seemed to be lower (ηp² = 0.495) in those who improved their time-to-exhaustion. The longer time-to-exhaustion following IPC seemed to be associated with a lower effort perception (ηp² = 0.380) and larger impairments in neuromuscular function, i.e. larger ΔMVT, ΔVA, and ΔPS10·PS100–1 (d = 0.71, 1.0, 0.92, respectively). IPC did neither affect exercise tolerance, performance fatigability, as well as its central and peripheral determinants, nor muscle activity, SmO2, and perceptual responses, during submaximal isometric exercise. However, IPC seemed to have an ergogenic effect in a few subjects, which might have resulted from a lower effort perception during exercise. These findings support the assumption that there are ‘responders’ and ‘non-responders’ to IPC.